Effect of prior fatiguing sport-specific exercise on field hockey passing ability - Hollville, E.; Le Croller, V.; Hirasawa, Y.; Husson, R.; Rabita, G.; Brocherie, F. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To evaluate the effect of multiple sets of repeated-sprint-ability (RSA)-induced fatigue on subsequent passing-skill performance in field hockey players. Methods: A total of 10 elite U-21 (under-21) male field hockey players performed 5 sets of a combination of RSA test (6 × 20 m, 20 s of passive recovery) followed by a 1-min passing-skill test (passing reception with subsequent passes at a predesigned target). Data on fastest sprint time and cumulated sprint time for RSA test; total number of balls played, targeted, and passing accuracy (number of balls targeted/total number of balls played) for passing-skill test; heart rate (HR), blood lactate concentration (BLa), and rating of perceived exertion (RPE) were collected throughout the protocol. Results: RSA performance was significantly impaired from set 1 to set 5 (fastest sprint time +4.1%, P < .001; cumulated sprint time +2.3%, P < .01). For a similar average number of balls played (12.8 [1.4]) during each set, number of balls targeted (-1.7%, P < .05) and passing accuracy (-3.1%, P < .05) decreased up to the third set before reimproving over the last 2 sets. Psychophysiological responses (HR, BLa, and RPE) progressively increased (P < .05) toward protocol cessation. The decrease in passing accuracy with increasing RSA cumulated sprint time was fitted to a 2nd-order polynomial function (r2 = .94, P < .05). Conclusion: Multiple-set RSA-induced fatigue was accompanied by passing-skill adjustment variation, suggesting a complex interaction between physiological and psychological/cognitive function to preserve passing skill under fatigued condition.